The concept of «Financial stability of banks» essence and features - Yu Shuang (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
Object of research is the banking system. Subject of research is theoretical and practical principles, aspects and approaches to ensuring the financial stability of the banking system. Purpose of qualification master's work is to examine the theoretical foundations of banks' activities, analyze approaches to organization, and search for directions for further development of the system of ensuring financial stability of banks in the current environment. According to results of the research, a systematized study, which is a synthesis of theory and practice, has been formed, and which represents a “road map” for the formation of an effective system for ensuring the financial stability of the banking system.
Концепт «Фінансова стабільність банків»: сутність та особливості
Scientific advisor: Pohorelenko Nataliia, doctor of economics, professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Economics; banking activities; financial stability; central bank; risk management; stress testing; financial security; problem assets